Integrity Scandals of Politicians: A Political Integrity Index. (4th May 2022) - Huberts, Leo; Kaptein, Muel; de Koning, Bart
Abstract: How often are politicians confronted with public allegations of integrity violations? Which types of violations, government levels, and parties do these scandals involve? The Political Integrity Index developed in The Netherlands offers information about the number and types of political integrity scandals in the country since 2013. This article presents a brief overview of the relevant literature on integrity and corruption and on political scandals, with a summary of the conceptual framework and methodology used in our research, as well as some of the results. In the years 2013–2019, 355 political integrity scandals were documented, primarily at the local level of government (79%), involving almost all political parties but with the liberal–conservative People's Party for Freedom and Democracy (Volkspartĳ voor Vrĳheid en Democratie [VVD]) most prominent (90 scandals), and containing all types of integrity violations, with as the most prominent type "misconduct in the private sphere" (30%). The topic of integrity scandals involving politicians is relevant but nearly absent in research on public integrity and corruption. This is a challenge and an invitation to researchers in other countries to do comparable research, which might result in a theoretically and practically useful international political integrity index. For that research, the framework of the Political Integrity Index seems useful.